Pengaruh Artificial Intelligence (AI) Terhadap Hasil Belajar Mahasiswa yang Dimediasi oleh Motivasi Belajar dan Kreativitas - Yassir, Muhammad; Saharuna (Jambura Journal of Educational Management, 2024)
This study aims to determine the influence of Artificial Intelligence (AI) on students' learning outcomes mediated by learning motivation and creativity in the Modeling and Simulation course at the Nobel Institute of Technology and Business, Indonesia. This research was conducted using an ex post facto research design, which is a type of research conducted after certain events or conditions have occurred. The research sample consisted of 60 students selected from the entire student population at the Nobel Institute of Technology and Business, Indonesia. Data collection in this study used questionnaires for the variables of students' perceptions of Artificial Intelligence (AI), learning motivation, and creativity, as well as a test for the learning outcomes variable. The validity of the four instruments was tested using the Gregory technique, and reliability was tested using Cronbach's Alpha. The collected data were analyzed using descriptive and inferential statistics (Path Analysis). The results of the study indicate that: (1) Artificial Intelligence (AI) has a significant direct influence on learning motivation, creativity, and learning outcomes, (2) Artificial Intelligence has a significant influence on learning outcomes mediated by learning motivation, and (3) Artificial Intelligence has a significant influence on learning outcomes mediated by creativity. Therefore, educational institutions can utilize the potential of AI to enhance students' learning motivation, creativity, and learning outcomes more effectively.